Optimalisasi Potensi Lokal Desa Ujong Tanoh Darat melalui Pembuatan Kerajinan Plastik dan Ecoenzyme untuk Kemandirian Ekonomi dan Lingkungan - Safrika Safrika; Rezqi Malia; Fitriyani Fitriyani; Julia Julia; Khalidin Khalidin (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service aims to optimize the use of local potential in Ujong Tanoh Darat Village, Meureubo District, West Aceh Regency, in order to improve community welfare and realize village independence. Local village potential, such as natural resources, cultural diversity, and rich local wisdom, have not been optimally utilized, one of which is the management of plastic and household waste. This program focuses on community empowerment through skills training in processing waste into products of economic value, such as handicrafts from plastic waste and ecoenzymes from organic waste. As a result, the community gains new skills that can increase family income, reduce plastic waste, and increase environmental awareness. In addition, this program creates new economic opportunities through marketing local products and strengthening cooperation between residents. The sustainability of this program is expected to continue to support village economic independence, with support from the village government in developing environmentally friendly local potential-based businesses.